Critical factors in designing a class of X-shaped structures for vibration isolation. (15th November 2019) - Jing, Xingjian; Zhang, Linli; Jiang, Guoqing; Feng, Xiao; Guo, Yingqing; Xu, Zhaodong
Highlights: A comparative study on several novel anti-vibration structures. Critical design parameters are revealed with experimental validation. A new understanding of the nonlinear dynamics of this class of anti-vibration structures. Abstract: A comparative study is conducted on a class of typical X-shaped structures to explore critical design parameters in passive vibration isolation. Several benchmark X-shaped structures are therefore studied, considering the effects of several critical structural parameters on potential vibration isolation performance in different cases. Theoretical calculations, finite element simulations and experimental results show that this class of X-shaped structures in vibration isolation is critically affected by the ratio between the horizontal displacement in the installed spring and the vertical displacement of the structure, which is further nonlinearly dependent on the values of other structure parameters. This critical design parameter can act as a convenient optimization objective for selecting structural parameters in various practical applications. The results of this study thus present a new understanding of the nonlinear dynamics of the X-shaped structures which can facilitate the design or parametric selection of these structures in practices.